Analysis of Little Millets by High-resolution Mass Spectroscopy Focusing the Components of Little Millets Effective in the Management of Diabetes Mellitus (Asian Journal of Pharmaceutics (AJP), 2023)
Diabetes mellitus, a metabolic disorder, poses significant health risks. For diabetics, weight loss, exercise, oralglucose-lowering medicines, effective diet can help them to achieve adequate glycemic control. Millets containmany types of antioxidant elements such as phenolic flavonoids, which are important in controlling glucose levelsin the body. Taking the millet diet physiologically helps to control the gluconeogenesis process. Little Millet ispossessing rich antioxidant properties which helps to prevent metabolic and lifestyle disorders such as obesity,diabetes, and retinopathy. Through UHPLC-Q-TOF-MS/MS system, major antidiabetic compounds are revealedsuch as hispidin, caffeine, aicar, ketotifen, maltitol, tacrolimus, and pipemidic acid. These compounds indirectlycontrol body metabolism to cope-up with diabetes mellitus